A focus on students' use of Twitter – their interactions with each other, content and interface. (July 2014) - Prestridge, Sarah
In their advertising campaigns, universities depict students using computers, laptops, mobile phones, iPads and tablets as learning devices. Regardless of the marketing used, there is value in enlisting the advantages of any medium that can aid deep thinking and increase student engagement. This study offers new knowledge about conceptualising Twitter as a knowledge construction tool leveraged through mobile devices. A qualitative approach was conducted to investigate the learning outcomes of students' use of Twitter when it was implemented as a learning device. The use of Twitter was investigated to provide insight into the ways students and instructors interacted in this environment, how the content was made active and how the functionality of the tool and its conceptualisation impedes and/or supports the learning process. The results indicate that student-initiated interaction supported by instructor use of participatory pedagogies enables substantive dialogue through Twitter and that paraphrasing was the most common way students made learning active.